Ontologia para modelos de negócios de redes sociais na internet: um ensaio teórico-exploratório - Degen, Yves (2009)
Currently, a profusion of solutions called Web 2.0 and social networks is causing a major impact on the development of the Internet, comparing to the 'dot-com' era in terms of growth, investment and excitement. These initiatives have in common a high degree of community building, creating and sharing of content by the user, among other features. It is believed that social networks represent a high innovative and disruptive potential for the society and the business world. However, how to turn social networks and Web 2.0 applications in self-sustaining businesses models remains a challenge for the market. This dissertation intends to support the understanding and approach of the theme by proposing a specific ontology for business models of social networks on the Internet. This is accomplished through the development of a theoretical essay with an exploratory bias, based on extensive but not exhaustive literature review covering business models, social networks and other related topics. The created ontology is then applied in the representation of business models of social networks on the Internet. This work also provides an overview of the Web 2.0 phenomenon, covering some of its main technological and socioeconomic characteristics